Art and devotion in the Missions of Paraná and Uruguay: The painting of the Virgin of the Mission of Acaray - Franco, Ana Elisa Burró (Advances in Social Sciences Research Journal, 2020)
The objective of this article is to make known, on the one hand, the vicissitudes of a forgotten image of the first Jesuit missions of the Province of Paraguay and, on the other, to shed more light on the history of Guarani missionary art of which only remnants are known, not without mixes of mistakes and confusion. The “Annual” Letters themselves are sometimes contradictory, which is understandable, since reporting on so many events in a territory as extended and little communicated as this province was can lead to confusing news, as we will see in the development of this article. An important clarification is that in the “Annual” Letters, the main source of this article, the Fathers were little or not at all interested in accurately describing images, altarpieces or sculptures of the missions, they do it very occasionally and even more rarely they mention the authors. It is evident that this is not the main objective of their narration, so as it is to refer to what concerns to the conversions and progress of the neophytes in the knowledge of the faith that they preached. The missionaries did not sign the works for an evident principle of humility; most of the works are completely anonymous. They were performed Ad Maiorem Dei Gloriam.